2016
DOI: 10.5195/cajgh.2016.228
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Contribution of BRCA Mutations to Early Onset and Familial Breast Cancer in Uzbekistan

Abstract: Introuduction:Breast cancer is the most common malignancy in women and affects approximately 1 out of 8 females in the US. Risk of developing breast cancer is strongly influenced by genetic factors. Germ-line mutations in BRCA1 and BRCA2 genes are associated with 5–10% of breast cancer incidence. To reduce the risk of developing cancer and to increase the likelihood of early detection, carriers of BRCA1 or BRCA2 mutations are offered surveillance programs and effective preventive medical interventions. Identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(33 reference statements)
1
2
0
Order By: Relevance
“…The authors concluded that the c.5266dupC mutation had a substantial contribution to BC incidences in Uzbek population. Hence, the c.5266dupC mutation was postulated to have the founder effect in their population (Abdikhakimov et al 2016) similar to other European countries (Burcoş et al 2013, Hartwig et al 2013) and Southern American country, Brazil (Ewald et al 2011).…”
Section: Discussionsupporting
confidence: 52%
“…The authors concluded that the c.5266dupC mutation had a substantial contribution to BC incidences in Uzbek population. Hence, the c.5266dupC mutation was postulated to have the founder effect in their population (Abdikhakimov et al 2016) similar to other European countries (Burcoş et al 2013, Hartwig et al 2013) and Southern American country, Brazil (Ewald et al 2011).…”
Section: Discussionsupporting
confidence: 52%
“…There is no evidence to date about the founder effect of BRCA1 c.5278-2del within different populations, whereas BRCA1 c.5266dup was reported as one of the most frequent PVs in Eastern and Central Europe [ 41 ] and North Africa [ 42 ]. It is also discussed as a founder mutation for the development of BC in Uzbek, Ashkenazi Jewish, Tatar and Russian populations [ 43 46 ]. Previous studies of the BRCA1 gene showed the absence of the c.5266dup PV in a cohort of 121 Kazakh patients with BC, mean age of 50.3 ± 11.5 years [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer risk in mutation carriers is modified by several risk factors that cluster in families, including genetic modifiers of risk that influence mutation penetrance (Chenevix-Trench et al, 2007). One of the major risk factors is a germline mutation in BRCA1 and BRCA2 which have an important role in hereditary breast-ovarian cancer in different populations (Abdikhakimov, Mukaddas, Bakhtiyar, & Shahlo, 2016;Celik et al, 2018;Harris, Morrow, & Bonadonna, 1993;Shahabi et al, 2017). In the Tunisian population, several studies have evaluated the association of these mutations in hereditary breast cancer patients (Belaiba et al, 2018;Fourati et al, 2014;Mahfoudh et al, 2012;Riahi et al, 2015;Troudi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%